2009
DOI: 10.1021/op900018f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Formation and Hydrolysis of N,N-Dimethylcarbamoyl Chloride (DMCC) in Vilsmeier Reactions Using GC/MS as the Analytical Detection Method

Abstract: The formation of N,N-dimethylcarbamoyl chloride (DMCC) in Vilsmeier reactions (VRs) and the hydrolysis of DMCC during aqueous workup were investigated. The amount of DMCC formed was dependent on the chlorination reagent. The activity order was found to be: thionyl chloride > oxalyl chloride > phosphorus oxychloride. The concentrations of DMCC found in the tested reactions were normally at a level of 0-20 ppm. In the presence of a base the level was higher. DMCC hydrolyzed quickly under aqueous workup condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…However, SOCl 2 is known to decompose to SO 2 Cl 2 and SCl 2 , and the latter can react with DMF to generate dimethyl carbamoyl chloride (DMCC), along with sulfur as the stoichiometric byproduct (Scheme ). , SCl 2 might also be a process impurity in SOCl 2 , since it is commonly used in the commercial production of SOCl 2…”
Section: Resultsmentioning
confidence: 99%
“…However, SOCl 2 is known to decompose to SO 2 Cl 2 and SCl 2 , and the latter can react with DMF to generate dimethyl carbamoyl chloride (DMCC), along with sulfur as the stoichiometric byproduct (Scheme ). , SCl 2 might also be a process impurity in SOCl 2 , since it is commonly used in the commercial production of SOCl 2…”
Section: Resultsmentioning
confidence: 99%
“…However, one disadvantage of thionyl chloride is the potential formation of dimethylcarbamoyl chloride, a known carcinogen in animal models, when used in combination with DMF as catalyst . The mechanisms for the formation of this side product are shown in Scheme …”
Section: Reagents For Amide Couplingmentioning
confidence: 99%
“…An analogous incident involving SOCl 2 /DMF was reported by Joshi in 1986, in which a sudden exotherm and pressure rise caused by spontaneous decomposition occurred in a 400 L reactor during vacuum distillation of a SOCl 2 /DMF mixture to remove SO 2 . In addition to SO 2 , sulfur (S), HCl, and N , N -dimethylcarbamoyl chloride (DMCC), a potent carcinogen that is heavily regulated in many countries with strict site volume limits, were also identified among the decomposition products. Thermal stability studies using an adiabatic calorimeter indicated that a runaway reaction occurred after 8 h at 60 °C, but after only 20 min when the mixture was maintained at 85 °C.…”
Section: Potential Safety Hazards With Dmfmentioning
confidence: 99%